2022
DOI: 10.1177/21582440221144436
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Knowledge, Attitudes, and Practices of Childhood Obesity in Singapore

Abstract: The obesity pandemic is increasingly threatening Asian populations. This is especially so for children from higher-income countries, such as Singapore. Among the various driving factors of obesity, parents’ health knowledge, attitudes, and practices are underexplored. The present study uses a nationally representative sample of 1,491 responses from Singapore to investigate parental knowledge, attitudes, and practices (KAP) about childhood obesity. Latent class analysis (LCA) on parents’ responses to the KAP su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…For an hour each morning, even on Sundays, he teaches her Braille, and in the afternoons, he takes her on his rounds. On Tuesdays, when the museum is closed, the father and daughter sleep much, drink sugared coffee, walk to different places, visit bookshops; when Mr. LeBlanc gifts her with a dictionary, a journal, or a magazine full of photographs, and promises to her that he will never leave her, not in a million years (Doerr, 2015: 31) Parents' dedication to remaining focused on the development of the child, either abled or disabled, has been seen as having a promoting influence on cognitive enrichment (Gomez et al, 2018;Platje et al, 2018;Straughan & Xu, 2022). Mr. LeBlanc's incessant contributions to help broaden Marie-Laure's inner sight as he makes her go through multiple riddles, puzzles, and surprises lead to noticeable outcomes in terms of enabling the blind child to face her life.…”
Section: Resultsmentioning
confidence: 99%
“…For an hour each morning, even on Sundays, he teaches her Braille, and in the afternoons, he takes her on his rounds. On Tuesdays, when the museum is closed, the father and daughter sleep much, drink sugared coffee, walk to different places, visit bookshops; when Mr. LeBlanc gifts her with a dictionary, a journal, or a magazine full of photographs, and promises to her that he will never leave her, not in a million years (Doerr, 2015: 31) Parents' dedication to remaining focused on the development of the child, either abled or disabled, has been seen as having a promoting influence on cognitive enrichment (Gomez et al, 2018;Platje et al, 2018;Straughan & Xu, 2022). Mr. LeBlanc's incessant contributions to help broaden Marie-Laure's inner sight as he makes her go through multiple riddles, puzzles, and surprises lead to noticeable outcomes in terms of enabling the blind child to face her life.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of sufficient awareness of parents was one of our noticeable findings. According to the key role of parents knowledge, attitudes, and practices, a national survey from Singapore reported that different parenting styles have a decisive role in children obesity [ 36 ]. And, we found lack of healthy eating style at home is a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive analyses were performed for the demographic data and KAP scores. A modified Bloom cutoff was used to define good knowledge, favorable attitude, and proactive practice as ≥70% of the maximum score for each dimension [ 24 , 25 ]. The continuous data were expressed as means ± standard deviations.…”
Section: Methodsmentioning
confidence: 99%